2019
DOI: 10.1016/j.eurpsy.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinography in psychiatry: A systematic literature review

Abstract: This review aims to consolidate the available information on use of electroretinography as a diagnostic tool in psychiatry. The electroretinogram (ERG) has been found to have diagnostic utility in cocaine withdrawal (reduced light-adapted b-wave response), major depressive disorder (reduced contrast gain in pattern ERG), and schizophrenia (reduced a- and b-wave amplitudes). This review examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…These findings indicate that the ERG is able to reveal differences in the nature of neural transmission that are governed by the same CNS neurotransmitters. The overlapping interactions of genes implicated in ASD and schizophrenia for instance (Hoerder-Suabedissen et al 2013;Pathania et al 2014) and similar changes of a-and b-wave amplitudes and b-wave time to peak in schizophrenia (Hébert et al 2020) and these reported in this study, suggests that the ERG could help our understanding of a diverse range of psychiatric disorders encompassing ASD, ADHD, OCD, schizophrenia and bipolar disorder , Youssef et al 2019. The ERG offers the potential to help our understanding of neurodevelopmental and neurodegenerative conditions as a non-invasive and objective measure of retinal activity in response to brief flashes of light (Schwitzer et al 2015;.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…These findings indicate that the ERG is able to reveal differences in the nature of neural transmission that are governed by the same CNS neurotransmitters. The overlapping interactions of genes implicated in ASD and schizophrenia for instance (Hoerder-Suabedissen et al 2013;Pathania et al 2014) and similar changes of a-and b-wave amplitudes and b-wave time to peak in schizophrenia (Hébert et al 2020) and these reported in this study, suggests that the ERG could help our understanding of a diverse range of psychiatric disorders encompassing ASD, ADHD, OCD, schizophrenia and bipolar disorder , Youssef et al 2019. The ERG offers the potential to help our understanding of neurodevelopmental and neurodegenerative conditions as a non-invasive and objective measure of retinal activity in response to brief flashes of light (Schwitzer et al 2015;.…”
supporting
confidence: 74%
“…It is known that the shape of the ERG is altered in some neurological diseases. A recent systematic review has highlighted the growing use of the ERG in psychiatric disorders and its potential for identifying conditions based on the ERG waveform (Youssef et al 2019). For example, schizophrenia (Hébert et al 2015) found smaller LA a-and b-wave amplitudes as well as a prolonged b-wave peak times, and in depression (Hébert et al 2017) reported a delayed cone b-wave time to peak.…”
mentioning
confidence: 99%
“…ERG has been performed in other neurodevelopmental diseases and psychiatric disorders [43][44][45][46] and offers an opportunity to non-invasively explore visual system physiology in individuals with intellectual disability and complex pathologies such as FXS. Indeed, a recent systematic review has highlighted the growing use of ERG in psychiatric disorders [46].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, electroretinography (ERG) has emerged as a non-invasive and reliable approach to investigate psychiatric disorders (Lavoie et al, 2014c;Youssef et al, 2019) given that the retina belongs to the central nervous system as they share the same embryonic origin (Graw, 2010;Dowling, 2012). The ERG is a biopotential signal generated by the retina in response to a flash of light.…”
Section: Introductionmentioning
confidence: 99%